The Influence of Leadership, Work Culture and Competence on Employee Performance at the Southeast Sulawesi Provincial Welfare Bureau - La Ode Muhammad Rickhzal Putra; Abd. Azis Muthalib; Nofal Supriaddin; Muh. Nur; Rince Tambunan (Syntax Idea)
This study aims to find out and analyze the influence of leadership, work culture and competence on employee performance at the Southeast Sulawesi Provincial Welfare Bureau. The determination of the number of samples in this study is by using the census method, namely the number of samples taken from the entire population of 46 employees. The data analysis technique in this study uses multiple linear regression analysis using Microsoft Excel, and SPSS software. Based on the results of the study, it can be concluded that (1) Leadership, work culture, and competence have a positive and significant effect on employee performance at the Southeast Sulawesi Provincial Welfare Bureau; (2) Leadership has a positive and significant effect on employee performance at the Southeast Sulawesi Provincial Welfare Bureau; (3) Work culture has a positive and significant effect on employee performance at the Southeast Sulawesi Provincial Welfare Bureau; and (4) Work culture has a positive and significant effect on employee performance at the Southeast Sulawesi Provincial Welfare Bureau.